The Role of Information and Communication Technologies (ICT) in Environmental Quality: An Empirical Analysis for South Asian Economies - Andlib, Zubaria; Khan, Adnan (International Journal of Economic and Environmental Geology, 2023)
Present study is an attempt to provide an in-depth understanding of the relationship between ICT, financial development, governance effectiveness, and COE nexus in selected South Asian countries. The data were acquired from WDI and applied FMOLS, DOLS, FEOLS methods of estimation for the period 1995-2019. It is observed that ICT has negative while financial development has a positive impact on COE in the case of four South Asian economies. Concerning the impact of governance on COE, it is observed that governance effectiveness is negatively associated with COE. It is evident from the empirical analysis that COE can be mitigated with effective governance policies.